The Existing Ginning System in the Cotton Ginning Industry (Texas Journal of Multidisciplinary Studies, 2022)
After the independence of Uzbekistan, radical market reforms were carried out in all sectors and industries, including agriculture and related industries, including the primary processing industry [1]. This, in turn, has significantly increased the quality of cotton fiber grown in the country, as well as the potential for state exports. During the years of independence, Uzbekistan has done a lot to grow cotton, process it and increase its competitiveness in the world market. Increasing the purchasing power of Uzbek cotton in regional and global markets through the production of consistent and high-quality cotton products has been identified by the state as a key priority. The main direction of the reforms is to ensure high yields of fiber from each cotton variety by reducing the cost of production